An Uncommon Feature of Chronic Granulomatous Disease in a Neonate - Razieh Afrough; Sayyed Shahabeddin Mohseni; Setareh Sagheb (Case Reports in Infectious Diseases)
Chronic Granulomatous Disease (CGD) represents recurrent life-threatening bacterial and fungal infections and granuloma formation with a high mortality rate. CGD’s sign and symptoms usually appear in infancy and children before the age of five; therefore, its presentation in neonatal period with some uncommon features may be easily overlooked. Here we describe a case of CGD in a 24-day-old boy, presenting with a diffuse purulent vesiculopustular rash and multiple osteomyelitis.